Improvement of a control system for a selective compliant articulated robot arm - Abalon, Adrian Alexander S. (2011)
Selective Compliant Articulated Robot Arms (SCARAs) are one of the many industrial robots used by manufacturing companies. Their heavy payload capabilities, which can be implemented at high speeds and small workspaces, make them very practical for pick-and-place operations. An improvement of the previously developed control system for the Adept Cobra 600 by Buyao and Nirza was made to enable the SCARA to perform tasks or commands like moving to a point accurately. Moving the robot arm to its nest position, moving the arm's joints, moving the arm's end-effector to a desired point, and changing the speed of movement of the robot arm are the basic commands that a robot arm control system should be able to implement. Linear power supplies, motor drivers and microcontrollers were designed, fabricated and programmed for the control system. The system will be used to control the four AC servo motors of the SCARA. Each servomotor is dedicated to manipulate one joint only. The improved control system for the Adept Cobra 600 was able to perform the basic commands for the robotic arm using a nearby computer to pass command arguments. The motor drivers were able to actuate the joints of the robot arm smoothly but the movements were limited to moving one joint at a time. The control program was able to read the encoder outputs properly. A graphical user interface was also developed to be able to provide easy usage of the robot arm.